PENGARUH CITRA PERUSAHAAN, KUALITAS LAYANAN DAN NILAI PELANGGAN TERHADAP KEPUASAN PELANGGAN DI PT CAKRAWALA ANTARA NUSANTARA CARGO BALI - I Komang Wira Kencana Putra; I G NG A Gede Eka Teja Kusuma; Ni Putu Cempaka Dharmadewi Atmaja (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar., 2023)
Today's marketing-related company goals have shifted from buyer acquisition to customer loyalty. This study aims to determine the effect of brand image, promotion and service quality on customer loyalty at the Furious Bali Distro. The population in this study are customers of the Furious Bali Distro. The sampling technique was carried out by purposive sampling method, so the number of samples in this study were 160 customers at the Furious Bali Distro. The data analysis technique used to answer the hypothesis is multiple linear regression analysis. The results of this study indicate that brand image has a positive and significant effect on customer loyalty at the Furious Bali Distro. Promotion has a positive and significant effect on customer loyalty at the Furious Bali Distro. Service quality has a positive and significant effect on customer loyalty at the Furious Bali Distro.